THE STUDENTSâ PERCEPTIONS TO THE IMPLEMENTATION OF ENGLISH ASSESSMENT (A Case Study at STAIN Palangka Raya) - Siminto, Siminto (LP2M IAIN Palangka Raya, 2008)
This study focuses on three questions: (1) How are the studentsâ perceptions to the implementation of English assessment? (2) How are the studentsâ perceptions to the items of English assessment? (3) How are the studentsâ perceptions to their scores in English assessment? Data were collected from the interview to the students (13 students). They were chosen based on the upper and lower scores. Purpose sampling was used in deciding of the students as the informants. Scores in this study were from the upper score (>400) and lower score (<400).Findings of the interview revealed that as follows: (1) Majority of the students consider that the implementation of English assessment was not effective yet. It was not effective meant that the performance of the English assessment had some problems. For examples: classroom, the number of the students, and time cases. The main problems were the preparation of the performance of English assessment was not ready, (2) Majority of the students had got problems in listening comprehension section. They could not listen to the cassette well. Responses of the students, only a few of the students did not have problems with listening comprehension section, and (3) Majority of the students got dissatisfactions to their scores. Statements indicated that their scores did not fulfill their expectation to the performance of English assessment. The other findings revealed that certification purpose of assessment is important, and students agree that assessment could aim to develop studentsâ capacity for current and future learning. Studentsâ perceptions of assessment practice also suggest that current assessment practice could develop their competence in English.Â